Labfiles #005 : Addictlab Chocolate Design Expo. - Van Mol, Jan; Addict Creative Lab (Brussels : Addict Ceative Lab, 2006)
Almeida, Rodrigo ; Azzimonti, Enrico ; Pigem, Jordi ; Baccarna, Bart ; Bar-Shay, Gili ; Bihr, Damien ; Blink ; Bormann, Anna ; Serman, Selma ; Bussgen, Christina ; De Gersem, Annamaria ; Fleischer, Silke ; Gruijters, Katja ; Gumdesign ; Velluto, Joe ; Kunkel, Julia ; Maeda, Kuniko ; Komoda, Kazuyo ; Maggio, Tommaso ; Moriceau, Laurent ; Nichetto, Luca ; Packd ; Quackers, Liv ; Van der Hallen, Luk.
Addictlab Chocolate Design Expo, Juventa House, Kortrijk, October 2006
kunstcatalogus